Reconstructing the Post-Pandemic Economic Legal Framework: Perspectives on Global Recovery and Stability - Arpiati, Arpiati (International Journal of Social Science, Education, Communication and Economics, 2025)
The global pandemic has drastically altered the global economic landscape, necessitating the reconstruction of economic legal frameworks to support global recovery and stability. This article outlines the importance of implementing flexible, innovative, and multilateral cooperation-oriented legal frameworks to address various post-pandemic challenges. An approach based on strengthening inclusive financial systems, digitalisation, and local economic empowerment is seen as the main solution to reduce inequality and promote a sustainable economy. By emphasising the principles of global justice and adaptation to change, the reconstruction of the economic legal framework is expected to not only ensure short-term recovery but also build long-term resilience in the face of future crises. This article offers a holistic perspective on the importance of updating the economic legal framework as a foundation for creating post-pandemic global stability.